KEMAMPUAN DOSEN DALAM MENYUSUN TES BERBASIS TEORI BLOOM DILIHAT DARI SENIORITASNYA DI FKIP UNIVERSITAS SLAMET RIYADI SURAKARTA TAHUN AKADEMIK 2014/2015 - Fadjeri, Sri Hartini (Widya Wacana: Jurnal Ilmiah, 2015)
This research aims at knowing whether there is differences in their competence in developingBloom theory-based tests based on seniority in Faculty of Education and Teachers Training inSlamet Riyadi Surakarta in 2014/2015 academic year.The population of this research is 36 out of 40 lecturers in Faculty of Education and TeachersTraining in Slamet Riyadi Surakarta which consists of 17 (with more than 10 years experience )senior lecturers and 19 junior lecturers (with less than 10 years experience). This researchapplies documentation method. The instruments used to analyzed the questions developed by thelecturers are designed based on Bloom theory. The data are analyzed based on mixed method.The quantitative data were analyzed with minitab to recognize whether there is difference incompetence between the senior and the junior. Meanwhile, the specific findings were analyzedbased on descriptive qualitative analysis.From the data analysis with Minitab the Tvalue is 2.33 with Pvalue 0.026< 0.05 meaning thatHo is rejected and the margin average is 0.731. It can be concluded that there is difference incompetence between senior and junior lecturers in developing Bloom theory-based tests. Anotherfindings in the research : 1 out of 19 junior lecturers did not develop the test based oncomprehensive criteria; 4 out of 19 lecturers (20%) only develop the test to level C3; 7 lecturers(40%) develop only to level C4; 6 lecturers (35%) develop only to level C5 and 1 leturer (5%)develop to level C6Meanwhile, among the senior, the findings are; 1 out of 17 lecturers (6%) develop the test only tolevel C3; 6 lecturers (36%) develop to level C4; 3 lecturers (18%) develop to level C5; 7lecturers (40%) develop to level C6. Based on the findings, both junior and senior lecturers needto improve their competence in developing test. LPM in the university is hoped to provide testdeveloping training for both lecturers.Keywords: competence in developing test, Bloom theory, test quality